Spectral-Luminescent Properties of Terbium-Containing Zirconomolybdates - Bair G. Bazarov (Конденсированные среды и межфазные границы, 2020)
To date, double molybdates of mono- and tetravalent elements have been comprehensively studied, and systems with molybdates of mono- and trivalent elements have been studied quite thoroughly. Some materials based on double molybdates, for example, those containing lanthanides, are considered promising for laser technology and electronics. Meanwhile, there is limited information on the properties, especially optical ones, of the molybdates containing rare-earth elements and zirconium. The aim of this work was to study the luminescent properties of self-activated terbium-containing zirconomolybdates with the compositions Tb2Zr3(MoO4)9 (1:3) and Tb2Zr(MoO4)5 (1:1), crystallising in two different structural types. Powder samples of the studied molybdates were synthesised by ceramic technology. The absorption, excitation, and emission spectra were measured using a Perkin Elmer Lambda 950 spectrophotometer. Luminescence was excited by a 250 W DKSSh-250 xenon lamp through an MDR-2 monochromator and recorded using an SDL-1 double monochromator with a grating of 600 lines/mm. The optical properties of new zirconium molybdates containing Tb3+ ions were studied. They revealed bright luminescence in the green spectral region due to the transitions inside the 4f shell of the rare-earth Tb3+ ion, excited both in the bands associated with the 4f-4f transitions and in the band with a charge transfer. The observed spectral lines as well as luminescence and excitation bands were identifi ed. It was shown that the position of the wide excitation band associated with the “charge transfer” transitions from O2– in MoO42– groups via Mo–O bonds to luminescent centres (Tb3+) does not depend on the matrix structure. The structure and intensity of the observed spectral lines, indicating a low symmetry of the Tb3+ crystalline environment, correlate with the structural analysis data. The results obtained in this work can be used when creating promising phosphors in the greenspectral region under ultraviolet excitation.